2019
DOI: 10.1021/acs.analchem.9b02469
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Au–Ag Janus Nanoparticle Engineered Ratiometric Surface-Enhanced Raman Scattering Aptasensor for Ochratoxin A Detection

Abstract: Ochratoxin A (OTA), a toxic mycotoxin, poses severe risks to environment and human health. Herein, we develop a ratiometric surface-enhanced Raman scattering (SERS) aptasensor based on internal standard (IS) methods for the sensitive and reproducible quantitative detection of OTA. Au−Ag Janus nanoparticles (NPs) are successfully synthesized under the guidance of 2-mercaptobenzoimidazole-5-carboxylic acid (MBIA), which possesses intrinsic Raman signals, thus no additional modification with a Raman reporter on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 40 publications
(62 reference statements)
0
96
0
Order By: Relevance
“…In 2019, two different Janus particle-based approaches were developed for the detection of ochratoxin A (OTA), a toxic mycotoxin produced by several Aspergillus and Penicillium species. Zhao et al reported on a ratiometric SERS (surface-enhanced Raman scattering) aptasensor for the quantitative detection of ochratoxin A based on plasmonic Au-Ag Janus nanoparticles [97]. The Au-Ag Janus NPs were fabricated via sequential growth of silver islands on gold cores.…”
Section: Toxin Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, two different Janus particle-based approaches were developed for the detection of ochratoxin A (OTA), a toxic mycotoxin produced by several Aspergillus and Penicillium species. Zhao et al reported on a ratiometric SERS (surface-enhanced Raman scattering) aptasensor for the quantitative detection of ochratoxin A based on plasmonic Au-Ag Janus nanoparticles [97]. The Au-Ag Janus NPs were fabricated via sequential growth of silver islands on gold cores.…”
Section: Toxin Detectionmentioning
confidence: 99%
“…The ligand 2-mercaptobenzoimidazole-5-carboxylic acid (MBIA) operates as a Raman reporter, while the Au-Ag Janus NPs enhance the SERS signal. The combination of these JPs with highly stable MXenes nanosheets allowed the introduction of an internal standard for quantitative analysis of ochratoxin A [97]. The Janus NPs were connected to the MXenes nanosheets via hydrogen bonds and chelation interaction between phosphate groups and titanium ions.…”
Section: Toxin Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBIA ligands guided the oriented growth of Ag islands, and exhibited amplified SERS signals due to the plasmonic coupling of Au heads and Ag islands. [69] A ratiometric SERS aptasensor was fabricated for OTA detection using SERS-active Au-Ag Janus NPs as detection probes and MXenes as reference probes (Ti 3 C 2 T x , T x represents the surface terminations of OH, F, O) (Figure 8d). In practical detection, sophisticated sampling pretreatment and purification procedures are necessary.…”
Section: Hazardous Substances Detectionmentioning
confidence: 99%
“…[21][22][23] As an example, Ti 3 C 2 (MXene) was used to combine with analyte molecules by hydrogen bonds, coordination bonds and van der Waals forces to achieve unique and stable Raman characteristic peaks for accurate quantitative detection, which had been used for Ochratoxin A application. [24][25][26][27] Similarly, because of its nanostructure and high electron mobility performance, molybdenum disulfide (MoS 2 ) related materials had also been reported for the detection of Rhodamine 6G with high SERS responses and accuracy. [28,29] In addition, the selection of reference signal was of vital importance to the sensitivity and stability in SERS detection.…”
Section: Introductionmentioning
confidence: 99%